(3JegjO GdaQT aj GdNUGd GdehLHI dXd GdYQTs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdYXje hHYO aEf GdMOjK GdeTghQ ai GdSHYI GdJi jXdge Gddg ai Xd YQTg hbO fXege GdTjN CHh TGeI ai HjJjf s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde jbhd Gddg YR hLd bQHhG Cgd dG Edg EdG Gddg ef Xd YQTi aEfi CMHge JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B483s
Keywords: (3Gdabg GdESdGejs